PERAN UNITED NATIONS HIGH COMMISSIONER FOR REFUGEES (UNHCR) DALAM MENGATASI PENGUNGSI DARI SUDAN SELATAN DI UGANDA - Arethusa, Zana Cobitha; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Role of the United Nations High Commissioner For Refugees (UNHCR) in dealing with South Sudanese refugees in Uganda. There was a humanitarian crisis that forced millions of people to leave their territories, especially the African and Middle Eastern regions, due to ethnic conflicts that caused South Sudanese to flee to the country of Uganda. The conflict greatly impacted the economy, environmental health, education, and water, many of them were affected by disease outbreaks due to the dense and slum housing conditions. The purpose of this research is to find out the role of the United Nations High Commissioner for Refugees (UNHCR) in dealing with refugees from South Sudan in Uganda. His research uses the perspective of Pluralism, Pluralism believes that the state is not the only actor in the international world. Therefore, international organizations such as UNHCR are involved in dealing with the South Sudanese refugee problem. The type of research used by the author is qualitative research with data processing in an analytical descriptive manner using library data collection techniques, namely utilizing secondary data obtained through literature studies that are sought from various literature such as books, journals, bulletins, newspapers, annual reports of several related agencies. , documents, or other materials. The government of Uganda is working with UNHCR as a UN humanitarian agency which aims to handle and provide protection for South Sudanese refugees. With various roles and collaboration with other organizations. UNHCR has tried to solve this problem properly. Keywords: Refugees, humanitarian crisis, ethnicity, International cooperation, UNHCR